Shalparni (Desmodium Gangeticum) – A Review from Pharmacological Perspective - kumari, Pramila; Imtiyaj, Mohd; Masum; Vijaya (International Research Journal of Ayurveda & Yoga, 2022)
Shalparni is a well-known plant in Ayurveda literature. The botanical name of Shalparni is Desmodium gangeticum DC., and belongs to the family Fabaceae. Shalparni is one of the constituent drug of Laghu panchmool and Dashmoola. Due to its madhura – tikta rasa and madhuravipaka it alleviates vitiated vaat and rakta dusthi, so it is indicated efficiently in vaatrakta chikitsa. In Charaka samhita it is classified in sothhara mahakashya and in Sushruta it is classified in Vidarigandhadi gana and laghupanchamula. Desmodidium gangeticum has many ethnomedical uses.In various nighantus, it is also indicated in Atisara, Shosha, Shopha, Jwara, Visha, Krimi rogas. Shalparni possesses aphrodisiac, cardiotonic, nervine tonic, febrifuge, haemostatic, and anti-helminthic properties. Shalparni also has anti-inflammatory, analgesic, antibacterial, anticholinesterase, smooth muscle relaxant, antipyretic, CNS stimulant and depressor, and bronchial muscle relaxant properties.